Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1183/09031936.04.00069004
|View full text |Cite
|
Sign up to set email alerts
|

Does systemic inflammation trigger local exercise-induced oxidative stress in COPD?

Abstract: Inflammatory abnormalities may be involved in the inadequate basal oxidant/antioxidant balance and local exercise-induced oxidative stress in chronic obstructive pulmonary disease (COPD) patients.The time course of oxidative stress and inflammation was investigated in 10 COPD patients and seven healthy subjects before and after local dynamic quadriceps endurance exercise at 40% of maximal strength. Venous samples were collected before, immediately after and up to 48 h after exercise.At rest, levels of an oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
78
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 38 publications
13
78
0
3
Order By: Relevance
“…In a sample of 10 subjects who had COPD, plasma levels of products of oxidative stress were increased significantly over similar products formed by seven controls at 6 hours after one episode of quadriceps endurance activity. Nonenzymatic antioxidants and inflammatory cytokine levels were unchanged by exercise immediately after and up to 48 hours after quadriceps endurance activity [97]. In this study, proinflammatory cytokines in plasma remained unchanged up to 6 hours after one episode of exercise.…”
Section: Oxidants Cytokines and Activitymentioning
confidence: 50%
“…In a sample of 10 subjects who had COPD, plasma levels of products of oxidative stress were increased significantly over similar products formed by seven controls at 6 hours after one episode of quadriceps endurance activity. Nonenzymatic antioxidants and inflammatory cytokine levels were unchanged by exercise immediately after and up to 48 hours after quadriceps endurance activity [97]. In this study, proinflammatory cytokines in plasma remained unchanged up to 6 hours after one episode of exercise.…”
Section: Oxidants Cytokines and Activitymentioning
confidence: 50%
“…KOECHLIN et al [25] found that CRP levels inversely correlated with endurance time. BROEKHUIZEN et al [23] also found that CRP increases in patients with poor exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this has been demonstrated in patients with COPD during exercise [107,108]. Physical exercise specifically increases plasma TNF-a levels in COPD [109].…”
Section: Underlying Mechanisms and Consequences For Treatment Of Compmentioning
confidence: 97%